Dealing with (Legitimized) Inequality: The Role of Ingroup Support to Resist Social Disadvantage - Jiménez-Moya, Gloria; Rodríguez-Bailón, Rosa; Spears, Russell; de Lemus, Soledad; Contreras, Camila (Psykhe, 2022)
Socially disadvantaged groups have to deal with diverse negative circumstances. We can expect that high status groups often legitimate and justify these disadvantages. However, when the low status group itself shares this perspective, it is more threatening: How do disadvantaged groups deal with social injustice when the ingroup itself frames it as deserved and legitimate? Previous studies have shown that under this circumstance, those individuals who highly identify with the ingroup reject the legitimacy norm and challenge their views instead by perceiving them as able to overcome and contest the disadvantage by collective means. In this work, we study the effect of a boundary condition, specifically the reliability of the norm of legitimacy. In one experimental study (n = 73), we expect high identifiers to contest the ingroup—as they frame their own disadvantage as legitimate—only if the reliability of the ingroup norm is weak, namely when a small (vs. large) ingroup sample supports it, as the chances to gather support amongst other ingroup members are better. However, when a large ingroup sample endorses the norm, high identifiers will accept this view, as the chances for success are low. We confirmed these hypotheses hinting that although high identifiers are expected to preserve ingroup interests, they might only do that when they can rely on ingroup support. This implies that, even though minorities are crucial to lead social change, the majority ingroup support is necessary in order to approach real changes.